Experiences in Northern Bobwhite Propagation and Translocation in Ohio, 1978-2012 - Mark J. Wiley; Nathan J. Stricker (National Quail Symposium Proceedings, 2017)
Ohio once boasted a population of 7 million northern bobwhites (Colinus virginianus). Catastrophic blizzards during 1976–1977 and 1977–1978 brought winter quail mortalities of 85% and 80%, respectively. Ohio’s bobwhite population was 430,000 in 1978, a 90% reduction from 1976. Remnant quail populations were small, isolated, and incapable of rapid recovery. The Ohio Department of Natural Resources (ODNR) initiated a statewide stocking effort to expedite population growth. The ODNR chose to propagate wild quail in captivity and release first-generation progeny (F1). Throughout 1980–1986, the ODNR released 65,000 F1 quail statewide. The ODNR monitored population response with North American Breeding Bird Survey, mail carriers, and roadside whistle-counts, but found little evidence of success. The ODNR evaluated postrelease survival and productivity of F1 hens (n = 100) and wild hens (n = 40) during 1984–1986 and deemed F1 hens inferior to wild hens. In 1993, the ODNR produced population models to develop minimum stocking rates for wild quail translocation, but insufficient numbers were captured. From 1998 to 2000 and 2005 to 2009, the ODNR translocated wild quail from Kansas to 5 Ohio sites with suitable, unoccupied habitat. Concurrently the ODNR translocated wild quail within Ohio. The ODNR conducted annual spring whistle-counts on all release sites during 1998–2012. Little or no evidence of sustained populations existed on sites after 7 years. Bobwhite translocation may yet show promise for population restoration, but evaluation should include 7–10 years of monitoring at a minimum.
Keywords: blizzard; Colinus virginianus; northern bobwhite; translocation; Ohio; propagation; population